Pengaruh Profitabilitas, Leverage, Firm Size, dan Earnings Power Terhadap Manajemen Laba Pada Perusahaan Sektor Properti Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Yusak Maleakhi Purnama; Eindye Taufiq (Magister Akuntansi FB-UK.Maranatha, 2021)
The purpose of this research is to obtain evidence regarding the effect of independent variable consisting of profitability, leverage, firm size, and earnings power towards dependent variable earnings management. The company used in this research is a property company that listed on the Indonesian Stock Exchange (IDX) from 2017-2019 with the criteria using purposive sampling method. The result of this research are profitability and earnings power has no influence on earnings management. However, leverage has a positive and significant influence on earnings management. Then, firm size has a negative and significant influence on earnings management. Keyword: Earnings Management, Profitability, Leverage, Firm Size, Earnings Power